Sustainable livelihoods for equine owners: Insights of working equines on pilgrimage route in Uttarakhand - Raut, Ajaykumar; YashPal,; Legha , Ram avtar; Dedar, Ramesh (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Working equines play an important role in the economy and culture of Uttarakhand. The present study on working equines in Uttarakhand found that many of these equids are not well-managed, which is leading to a decline in their health and welfare. They are used for transportation, pilgrimage and tourism. However, the use of working equines in Uttarakhand is facing several challenges, including lack of access to veterinary care, lack of insurance facility, lack of awareness, ignorance and limited opportunities for training, animal identification system and rest spots and veterinary camps. The study recommends awareness campaigns and training for equine owners, provision of better facilities to improve the management of working equines in Uttarakhand. In addition, access to credit, market linkages and government support are important for the sustainable livelihood of equine owners. The administrators, policy planers and other stakeholders can help to ensure that working equines in Uttarakhand are well-managed and that their owners can sustain their livelihoods by implementing the recommendations of the study. This will not only benefit the animals, but it will also benefit the pilgrimage, tourism, local economy and the environment.
Keywords: Equine; Management practices; Equine welfare; Working equines